2022
DOI: 10.1037/vio0000444
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, personality, and demographic factors: A moderated mediation of chronic violence exposure and violent offending in justice-involved youth.

Abstract: Objective: Guided by continuous traumatic stress theory (Eagle & Kaminer, 2013) and trauma coping theory (Ford et al., 2006), the present study examined hostility and callous-unemotional traits as mediators between chronic community violence exposure in adolescence and violent offending in early adulthood. Method: Baseline surveys and data over 5 years (8 follow-up time points) were analyzed from 1,354 justiceinvolved adolescents (86% male) Ages 14-19 (M = 16.04, SD = 1.14) in the Pathways to Desistance Projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This disruption, in turn, can interfere with the typical development of cortical areas (Stiles 2017; Vasung et al 2019) associated with the cognitive control system. The same principles can be applied to factors linked to attributes of crime hot spots, such as exposure to chronic community violence exposure and criminal acts on the streets, as well as physical factors that are known to contribute to persistent stressors (McEwen 2017; Sargent et al 2022), which, in turn, has the potential to disrupt the natural processes of neuron proliferation and differentiation, giving rise to neural circuits that underlie emotional and cognitive functions associated with antisocial behaviours, such as aggressiveness and externalizing disorders (Chong et al 2022; Palumbo et al 2018; Saxbe et al 2018; Tremblay, Vitaro, and Côté 2018).…”
Section: Interaction Between Crime Hot Spots and Neural Maturationmentioning
confidence: 99%
“…This disruption, in turn, can interfere with the typical development of cortical areas (Stiles 2017; Vasung et al 2019) associated with the cognitive control system. The same principles can be applied to factors linked to attributes of crime hot spots, such as exposure to chronic community violence exposure and criminal acts on the streets, as well as physical factors that are known to contribute to persistent stressors (McEwen 2017; Sargent et al 2022), which, in turn, has the potential to disrupt the natural processes of neuron proliferation and differentiation, giving rise to neural circuits that underlie emotional and cognitive functions associated with antisocial behaviours, such as aggressiveness and externalizing disorders (Chong et al 2022; Palumbo et al 2018; Saxbe et al 2018; Tremblay, Vitaro, and Côté 2018).…”
Section: Interaction Between Crime Hot Spots and Neural Maturationmentioning
confidence: 99%
“…For example, results from the Crossroads Study—a longitudinal study of a diverse sample of male first‐time juvenile offenders from California, Pennsylvania, and Louisiana—indicated that CU traits mediated the relation between exposure to violence and overt aggression (Wall Myers et al, 2018). In the Pathways to Desistance study—a longitudinal study of adjudicated youth from Pennsylvania and Arizona—CU mediated the association between witnessing violence and later aggressive offending (Sargent et al, 2022), and psychopathy—a broader construct that incorporates CU as well as impulsivity/irresponsibility and grandiosity/manipulativeness—mediated the association from earlier violence exposure to later violent offending for males (Baskin‐Sommers & Baskin, 2016). It should be noted that another set of analyses from a subset of these data found that exposure to violence mediated the association between CU and aggression for males, rather than CU mediating the association between exposure and aggression (Walters, 2018).…”
Section: Cu Traits and Aggressive Behaviormentioning
confidence: 99%